565 – Safety and pharmacokinetic profiles of a humanized monoclonal antibody TQH2722 targeting interleukin 4 receptor alpha (IL-4Rα) in health adult subjects - Lin, Pingping; Sun, Feifei; Xu, Yi; Ban, Rongxin; Jiang, Xin; Fu, Yao; Gao, Xiaomeng; Cao, Yu (British journal of dermatology (1951), 2024)
Introduction/Background TQH2722 is a humanized monoclonal antibody targeting interleukin 4 receptor alpha (IL4Rα) which leads to the dual-blockade of interleukin-4 (IL-4) and interleukin-13 (IL-13) signaling, inhibiting the T-helper cell type 2 immune pathway. Th2 inflammation is implicated in the pathobiology of diseases such as asthma and atopic dermatitis. We describe the safety and pharmacokinetic results from a first-in-human study in healthy subjects. Objectives To evaluate the safety, tolerability, pharmacokinetic characteristics, and immunogenicity of TQH2722 injection in healthy adult subjects. Methods This randomized, double-blind, placebo-controlled, ascending-dose phase I study (NCT05409326) was conducted in China. Each adult subject received a single subcutaneous (sc.) TQH2722 dose or placebo in single ascending-dose (SAD) cohorts, and 4 doses of TQH2722 or placebo administrated Q2W in multiple ascending-dose (MAD) cohorts. Pharmacokinetic samples were collected prior to first dose administration through 56 days after initial dosing in SAD cohorts. In the MAD cohorts, samples were collected before every administration until 56 days after last dosing. Results As of 28 September 2023, all subjects had completed the study, with the database locked while remaining unblinded. Sixty-six (66) healthy subjects were enrolled in this study. The SAD cohorts consisted of single doses of TQH2722 of 50 mg (n-4), 150 mg (n=10 active, 2 placebo), 300, 600, and 1200 mg cohorts, each receiving TQH2722 (n=8) or placebo (n=2). Ten subjects were enrolled in each of the 150 and 600 mg MAD cohorts receiving TQH2722 (n=8) or placebo (n=2). No dose-limiting toxicities or SAEs were observed and only 3 subjects experienced a grade 3 AE including 1 subject of increased triglycerides, 1 subject with increased creatine kinase and 1 subject with decreased blood potassium). All other AEs were of grade 1 or 2. The incidence and severity of AEs were not dose dependent. No SAEs or AEs led to treatment discontinuation. The pharmacokinetics of TQH2722 were indicative of an anti-receptor mAb in that TQH2722 exhibited nonlinear target-mediated clearance. Maximum serum concentration was reached after 2.78-6.75 days with the half-life of a single sc. administration of TQH2722 increasing by dose level, ranging between 4 and 18 days. Conclusions TQH2722 was safe and well tolerated in healthy volunteers. Injection site reactions and laboratory abnormalities were the most reported AEs, with grade 1-2 as the major severity. Most AEs resolved on their own. Single dosing showed non-linear increases of the drug exposure as the dosage increased. These data support further clinical development of TQH2722 as a therapeutic treatment for patients with Atopic Dermatitis and other related diseases mediated by Th2 inflammation.